2004
DOI: 10.1590/s1678-97412004000300006
|View full text |Cite
|
Sign up to set email alerts
|

<![CDATA[<b>Assessment of a new technique of hemoconcentration and the necessities of blood derivates for transfusion in patients submitted to heart surgery using cardiopulmonay bypass</b>]]>

Abstract: Objective: To assess a new technique of hemoconcentration and the necessity of blood component transfusion.Method: Eighty-six male (61.4%) and 54 female (38.6%) patients submitted to heart surgery under cardiopulmonary bypass were divided into two groups of 70 patients each according to conventional technique of blood preparation (Group A) and the use of the new technique of hemoconcentration (Group B).Results: The hemoconcentration technique is feasible and did not alter the intra-and postoperative complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Souza & Braile [25] developed a study to evaluate a technique of hemoconcentration during heart surgery with CPB with and without a hemoconcentrator and the necessity of blood components transfusion in patients. They verifyed that this technique of hemoconcentration used during on-pump heart surgery was efficacious in the removal of fluids and allowed a greater utilization of the blood remaining in the oxygenator and a lesser necessity of blood component transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Souza & Braile [25] developed a study to evaluate a technique of hemoconcentration during heart surgery with CPB with and without a hemoconcentrator and the necessity of blood components transfusion in patients. They verifyed that this technique of hemoconcentration used during on-pump heart surgery was efficacious in the removal of fluids and allowed a greater utilization of the blood remaining in the oxygenator and a lesser necessity of blood component transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on the use of hemoconcentration in cardiac surgery with ECC have concluded that the main advantages are removal of the macromolecules that mediate the systemic inflammatory reaction, reduction of circulating endotoxins, elimination of excess body water and pulmonary hypertension 15,16 .…”
Section: Discussionmentioning
confidence: 99%